The Role of Loneliness on Subjective Well-Being in Adolescents - Angelina Angelina; Andiny Shausan; Erik Wijaya (PT Publikasiku Academic Solution, 2024)
Loneliness is an experience that can have far-reaching effects on individuals, especially adolescents, who are in an important developmental phase. Subjective well-being, which includes positive emotions, life satisfaction, and emotional experiences, is an important indicator in assessing adolescents' mental health. This study aims to explore the role of loneliness in influencing subjective well-being in adolescents. This study used a quantitative approach with a survey design, involving 300 adolescent respondents aged 13-18 years. Data were collected through an online questionnaire consisting of the UCLA Loneliness Scale and Diener's Subjective Well-Being Scale. The results of the analysis show that loneliness has a significant negative influence on subjective well-being, with a coefficient of determination (R²) value of 0.314. This shows that 31.4% of the variation in subjective well-being can be explained by the level of loneliness. This study indicates that increased levels of loneliness are associated with decreased subjective well-being in adolescents. The findings provide important insights for the development of interventions aimed at improving adolescents' psychological well-being and reducing feelings of loneliness.